Neuropathy Dermatitis following Surgical Nerve Injury. (29th January 2012) - Sharquie, Khalifa E.; Noaimi, Adil A.; Alaboudi, Ali S.
Abstract : Background . Cutting nerve during operations like saphenous vein grafting and knee joint surgery are common surgical procedures. Objective . To report cases of dermatitis at the site of neuropathy following skin incision for saphenous vein grafting and knee joint surgery. Patients and Methods . This case report work was done in the Department of Dermatology, Baghdad Teaching Hospital, during 2009-2010, seven cases were recorded, six following saphenous vein grafting and one case after knee surgery. Five males and two females, their ages ranged from 50 to 66 (58 ± 5.033223) years. Detailed history and full clinical examination were done for each patient regarding all points related to their conditions. Results . All cases presented around 2-3 months following the operation with dermatitis at the site of operational incision. The dermatitis appeared on one side of the operational scar and at area of neuropathy, and the rash did not cross to contralateral side. The dermatitis was well-defined plaque or patch erythematous slight scaly and nonitchy and subsided within few weeks with or without topical therapy. Conclusions . Neuropathy dermatitis is apparently a new variant of dermatitis that follows nerve cut during surgery.